Icisungu – Divining Mother Earth in the Bemba Puberty Rite - Mutale Mulenga Kaunda (Journal for the Study of Religion, 2025)
Bemba culture celebrates two distinct rites for young women. The first rite is celebrated at puberty (icisungu) and the second is celebrated at marriage (imbusa). This article focuses on the first rite called icisungu when the girls reach puberty. The significance of icisungu rite is its centrality in possible promotion of female agency and reproductive health awareness among Bemba girls. This is vital as it establishes a solid connection between the cultural practices and their relevance in contemporary discussions about sexual reproductive health. Young girls are separated during icisungu in order to receive instruction on their journey into womanhood and how to safeguard themselves from early childhood debut into sexual activity. Icisungu is a safe space for young girls to learn agency and comprehensive sexuality education. Using African feminist cultural hermeneutics and mothering as a framework, this article demonstrates how the divine, mother earth and Bemba women offer agency.